High spatial resolution soil data for watershed modeling: 1. Development of a SSURGO-ArcSWAT utility - Sheshukov, Aleksey Y.; Daggupati, Prasad; Douglas-Mankin, Kyle R.; Lee, Ming-Chieh (My University, 2012)
Modeling of watersheds greatly benefits from high spatial resolution soil data. Watersheds models need to be compatible with a format in which soil data are stored. In the United States, the Soil Survey Geographic (SSURGO) database provides higher-spatial resolution soil data, but AVSWAT and ArcSWAT, two GIS-enabled interfaces for preparation of input data and post-processing for the Soil and Water Assessment Tool (SWAT) model, are compatible only with the State Soil Geographic (STATSGO) database, which is normally prepared at 10 to 20 times coarser scale. Available SSURGO processing tools currently work with AVSWAT, but not with the latest version of ArcSWAT. The objective of this study was to develop and demonstrate a utility for ArcMap GIS that is capable of processing SSURGO soil data into a modified STATSGO format that is readable by ArcSWAT. The SSURGO-ArcSWAT utility was applied to the State of Kansas, USA to test for regional differences between STATSGO and SSURGO databases in identification of soil hydrologic attributes. The utility was successful in translating SSURGO soil data into a format useable in ArcSWAT. When SSURGO data were compared with STATSGO data for the State of Kansas, about one-third of the total area had different soil hydrologic group classification, with greater than 10% differing by more than one group. Use of the SSURGO-ArcSWAT tool by watershed modelers will allow simple implementation of SSURGO data into ArcSWAT modeling projects.
Keywords: ArcObjects; GIS; Hydrologic Modeling; Soil database; SSURGO; STATSGO; SWAT